Processing and Properties Analysis of Grain Foods - Li, Yonghui (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Foods derived from grains and grain-based ingredients represent a crucial source of energy and nutrients for humans. Cereals are conventional food materials, while interest is growing in the utilization of pseudocereals, pulses, oilseeds, and other grains to develop various foods and food ingredients. Grain and food processing converts raw grains into functional ingredients and creates palatable and nutritious end-products. During processing, various physical and chemical changes and interactions take place, affecting the nutritional, textural, sensory, and other quality properties of the products. Methods, protocols, and equipment have been developed to process, monitor, and control processing parameters to achieve the desired end-product quality or functionality. This reprint covers diverse topics related to grain-processing innovations and the effect of both conventional and innovative grain processes on the properties of grain-derived ingredients, intermediates, and end products.